A western professor in Singapore: Cross-cultural readings, expectations, and surprises in the classroom. (August 2015) - Freeman, Bradley
The educational field is seeing an increased growth in English-language teaching opportunities abroad. This situation gives rise to a number of interesting research inquiries. For example, can teaching experience in one cultural context translate well into another? What do studies tell us about cross-cultural awareness and effectiveness of those teaching abroad and their students' proficiencies? This article introduces readers to literature that, while not always within the direct scope of international education, is made relevant given the specific case of an American professor's teaching experience abroad in Southeast Asia. The article is a case study comparing systems and discussing various literature related to cross-cultural matters, while also proposing multi-disciplinary research paths to explore.